Pengembangan Sistem Informasi Alumni Terintegrasi Menggunakan Teknologi Artificial Intelligence (AI) di Institusi Pendidikan Tinggi - William Evan Bunyamin; Calandra Alencia Haryani; Andree E. Widjaja; Ferry Vincentius Ferdinand; Brian Alvin Hananto; Hery (Jurnal Ilmiah Teknik Informatika (TEKINFO), 2026)
Currently, the Universitas Pelita Harapan Alumni Association (IKA UPH) faces data integration challenges dueto the absence of a centralized system. This study aims to design and develop an integrated alumni informationsystem using artificial intelligence (AI) technology in a higher education institution. The system developmentprocess utilizes the Rapid Application Development (RAD) methodology, leveraging the Laravel framework,MySQL database, and the integration of the Google Gemini 2.0 Flash API to support an AI chatbot feature. Thisinformation system features several core functionalities, including a job vacancy portal, event management,membership tracking, news updates, and an AI-based virtual assistant. To ensure system validity, testing wasconducted using the black-box method, the results of which indicate that all functional requirements for varioususer roles have been successfully met. Through the implementation of this platform, it is expected that alumnidata governance will become more structured, synergy and collaboration among alumni will enhance, andaccess to professional career opportunities will be wider for all community members.